2012
DOI: 10.1007/s00586-012-2477-7
|View full text |Cite
|
Sign up to set email alerts
|

Does brace treatment impact upon the flexibility and the correctability of idiopathic scoliosis in adolescents?

Abstract: Purpose Brace treatment has served as a vital non-surgical procedure for immature adolescent idiopathic scoliosis (AIS) patients with a mild or moderate curve. For the patients who fail in bracing and resort to surgery, it is unclear whether prior full-time brace treatment significantly influences outcomes. This study aims to investigate whether prior brace treatment has a negative impact upon the flexibility and correctability of the main curve in patients with AIS. Methods The participants were collected fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 38 publications
0
18
0
Order By: Relevance
“…Wang et al [9] indicate a small and insignificant decrease in the flexibility and correction of the primary curve after the surgical procedure in patients with a prior history of brace treatment compared to patients who had not been treated with a brace. History of preoperative brace treatment has not negative impact on postoperative self-perceived quality of life [9,3]. The presented study indicates that earlier treatment with a SpineCor dynamic brace does not have a significant effect on the amount of correction obtained through surgery.…”
Section: Discussionmentioning
confidence: 64%
See 3 more Smart Citations
“…Wang et al [9] indicate a small and insignificant decrease in the flexibility and correction of the primary curve after the surgical procedure in patients with a prior history of brace treatment compared to patients who had not been treated with a brace. History of preoperative brace treatment has not negative impact on postoperative self-perceived quality of life [9,3]. The presented study indicates that earlier treatment with a SpineCor dynamic brace does not have a significant effect on the amount of correction obtained through surgery.…”
Section: Discussionmentioning
confidence: 64%
“…The authors report satisfactory correction in both groups. However, they observe that a history of brace treatment has a negative impact on the correction of scoliosis, regardless of the type of curve, less visible in main thoracic curve [3]. Wang et al [9] indicate a small and insignificant decrease in the flexibility and correction of the primary curve after the surgical procedure in patients with a prior history of brace treatment compared to patients who had not been treated with a brace.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The current study confirmed the predictive value of RVAD and CRVA for the effectiveness of bracing in early AIS patients. Moreover, measurements of initial RVAD and CRVA before bracing can help to more accurately identify patients who are at higher risk of curve progression, thus to refine the indications and the protocols of brace treatment, because of the potential drawbacks of brace treatment, such as affecting the quality of life [31], reducing the flexibility of the spine [32], and so on. In addition, serial measurements of RVAD and CRVA provide constant assessments of the risk of curve progression, which are certainly more accurate and more reliable than that the measurements at brace initiation.…”
Section: Role Of Rva Measurements In Predicting Curve Progressionmentioning
confidence: 99%